Synthesis, microstructure, optical and field emission studies of iron vanadium oxide nanosheets - Badadhe, Satish S.; Suryawanshi, Sachin R.; Naphade, Rounak A.; Chaudhary, Minakshi V.; More, Mahendra A.; Shelke, Manjusha V.; Ogale, Satishchandra B. (Journal of Physics D-Applied Physics, 2016)
We report a single step growth of thin graphene-like, densely packed FeV3O8 (FVO) nanosheets on silicon substrates via facile hydrothermal synthesis. These nanosheets have dimensions of a few microns with thin edges, offering very high aspect ratio. These FVO nanosheets exhibit excellent field emission behaviour with low turn on and threshold voltages of 1.3 V mu m(-1) and 1.7 V mu m(-1), respectively. The corresponding emitter delivers high emission current density of (similar to 1.650 mA cm(-2)) at fairly low applied field (similar to 4.00 V mu m(-1)).
Keywords: FeV3O8; field emission; nanosheets